Documentary review of strategic planning within Public Management - Orlando Muñoz López, Juan; Emilio Escudero Vilchez, Fernando; Liliana Salazar Llerena, Silvia (Seven Editora, 2023)
OBJECTIVE: The main purpose of this research was to make a documentary review with the aim of making known the importance of a strategic plan within public management, since today carrying out such management requires many elements to become satisfactory. in all aspects. In other words, every company needs good organization and adequate control that can be achieved with a strategic management approach. METHODOLOGY: The methodology used in this article has been under a quantitative approach, through the review of varied bibliography of national and international organizations as well as authors referring to the information previously investigated by them. RESULTS: As a result, it was evidenced that the use of the documentary review of strategic planning helps in public management by allowing plans, strategies and national policies to be carried out that are aimed at satisfying the needs presented by citizens. CONCLUSION: Finally, it is concluded that, at the international level, many companies, whether public or private, have presented a tendency to take into account strategic planning, since it favors their growth and development. DOI: 10.56238/pacfdnsv1-030